Abrasive water jet piercing of inclined holes on ceramic coated nickel superalloy: A preliminary study. (October 2020) - Yuvaraj, N.; Arunkumar, N.; Nivetha, M.S.; Lina Esther, A.
Abstract: Micro inclined holes are widely used as cooling holes in the jet engine and gas turbine components for its protection from a high temperature gas stream. Usually, these components were made of thermal barrier coated (TBC) nickel superalloy as which often high corrosion and thermal fatigue resistance. In this work, the small diameter cooling holes with different inclination angles were fabricated on TBC nickel superalloy using the Abrasive Water Jet (AWJ) through a piercing mode. Different holes were fabricated through the employment of different settings of AWJ operational parameters namely jet impingement angle, stand-off distance and abrasive mass flow rate. The effect of piercing parameters on machining time, hole entry diameter and surface morphology were examined. From the experimental results, it is confirmed that the inclined hole surfaces do not contain any cracks and delamination. However, the rough morphology i.e wear tracks and microchips was seen in the hole wall surfaces. The preliminary results confirmed that the AWJ has capable for the production of cooling holes than other processing techniques based on lesser machining time and satisfactory hole quality. Yet, the further investigations would be required for comprehensive study of hole geometrical and surface features, and optimization of it.